Nurses: Katie Goes to College - Paul, Bette (Scholastic, Inc., 1995)
It's the moment Katie's been dreaming of for years. At last she's off to nursing college. And she's determined to make the very most of being a student$1! =s
Keywords: Girls and Women; Juvenile Fiction